The clinical significance of the intraoperative pathological examination of bilateral recurrent laryngeal nerve lymph nodes using frozen sections in cervical field lymph node dissection of thoracic esophageal squamous cell carcinoma - Xu, Jinxin; Zheng, Bin; Zhang, Shuliang; Zeng, Taidui; Chen, Hao; Zheng, Wei; Chen, Chun (Journal of Thoracic Disease, 2019)
Background: The aim of this study was to evaluate intraoperative pathological examination of the left and right recurrent laryngeal nerve lymph nodes (LNs) using frozen section as a predictor of cervical LN metastasis. Methods: Retrospectively collected data from 69 patients with esophageal squamous cell carcinoma who had undergone intraoperative pathological examination of the left and right recurrent laryngeal nerve LNs using frozen sections and three-field LN dissection in the Fujian Medical University Union Hospital from December 2015 to April 2018, was used to explore the relationship between recurrent laryngeal nerve LN metastasis and cervical LN metastasis and to determine whether cervical-field LN dissection should be performed in patients with thoracic esophageal cancer. Results: In the entire cohort, 15.9% (11/69) of patients had metastasis in the cervical LNs. We detected 1,195 cervical LN, with an average of 17.3 LN dissections per patient; 28 (2.3%) cases had LN metastasis. Patients with recurrent laryngeal nerve LN metastasis tended to have a high incidence of cervical LN metastasis (P=0.017). Multivariate analysis showed that left recurrent laryngeal nerve LN metastasis was the only independent risk factor for cervical LN metastasis (P=0.02). The incidence of postoperative pulmonary infection was 18.8% (13/69), chylothorax was 2.9% (2/69), anastomotic leakage was 2.9% (2/69), and hoarseness was 8.7% (6/69) for the entire cohort. There was no significant increase in complications compared with patients with 2-field LN dissection in our hospital during the same period. Additional studies are necessary to establish postoperative locoregional recurrence rates and long-term survival. Conclusions: Intraoperative pathological examination of left recurrent laryngeal nerve LN using frozen sections has some prognostic value in predicting cervical LN metastasis and it can be an indicator for the selection of cervical-field dissection in thoracic esophageal carcinoma.